Potent Inhibition of Ribulose-Bisphosphate Carboxylase by an Oxidized Impurity in Ribulose-1,5-Bisphosphate - Kane, Heather J. (American Society of Plant Physiologists, 1998)
Oxidation of d-ribulose-1,5-bisphosphate (ribulose-P(2)) during synthesis and/or storage produces d-glycero-2,3-pentodiulose-1,5-bisphosphate (pentodiulose-P(2)), a potent slow, tight-binding inhibitor of spinach (Spinacia oleracea L.) ribulose-P(2) carboxylase/oxygenase (Rubisco). Differing degrees of contamination with pentodiulose-P(2) caused the decline in Rubisco activity seen during Rubisco assay time courses to vary between different preparations of ribulose-P(2). With some ribulose-P(2) preparations, this compound can be the dominant cause of the decline, far exceeding the significance of the catalytic by-product, d-xylulose-1,5-bisphosphate. Unlike xylulose-1,5-bisphosphate, pentodiulose-P(2) did not appear to be a significant by-product of catalysis by wild-type Rubisco at saturating CO(2) concentration. It was produced slowly during frozen storage of ribulose-P(2), even at low pH, more rapidly in Rubisco assay buffers at room temperature, and particularly rapidly on deliberate oxidation of ribulose-P(2) with Cu(2+). Its formation was prevented by the exclusion of transition metals and O(2). Pentodiulose-P(2) was unstable and decayed to a variety of other less-inhibitory compounds, particularly in the presence of some buffers. However, it formed a tight, stable complex with carbamylated spinach Rubisco, which could be isolated by gel filtration, presumably because its structure mimics that of the enediol intermediate of Rubisco catalysis. Rubisco catalyzes the cleavage of pentodiulose-P(2) by H(2)O(2), producing P-glycolate.